2020
DOI: 10.1186/s13023-020-01530-5
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial on the efficacy and safety of pantethine in children with pantothenate kinase-associated neurodegeneration: a single-arm, open-label study

Abstract: Objective This study aimed to explore the efficacy and safety of pantethine in children with pantothenate kinase-associated neurodegeneration (PKAN). Methods A single-arm, open-label study was conducted. All subjects received pantethine during the 24-week period of treatment. The primary endpoints were change of the Unified Parkinson’s Disease Rating Scale (UPDRS) I–III and Fahn–Marsden (FM) score from baseline to week 24 after treatment. Results Fifteen children with PKAN were enrolled, and all patients c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Although in a recent clinical trial, FOsmetpantotenate Replacement Therapy (FORT) was shown not to be very effective 62 . In another single-arm, open-label study, pantethine was shown to delay the progression of motor dysfunction in children with PKAN, but not rescue 63 . Certain beneficial effects to PD are observed with therapies in our current studies.…”
Section: Discussionmentioning
confidence: 97%
“…Although in a recent clinical trial, FOsmetpantotenate Replacement Therapy (FORT) was shown not to be very effective 62 . In another single-arm, open-label study, pantethine was shown to delay the progression of motor dysfunction in children with PKAN, but not rescue 63 . Certain beneficial effects to PD are observed with therapies in our current studies.…”
Section: Discussionmentioning
confidence: 97%
“…Other efforts to treat PKAN include supplementation with CoA, pantethine, P-PaSH, and acetyl-P-PaSH ( 13 , 50 , 51 , 52 ) to compensate for the reduced levels of the metabolic intermediates of CoA caused by altered Pank2 activity. 4′-Phoshphopantetheine was found to be the most effective of these compounds because it is both orally bioavailable and able to cross the blood–brain barrier ( 13 ).…”
Section: Therapeutic Strategies For Pkanmentioning
confidence: 99%
“…Pantethine is currently used as a nutritional supplement in patients with hyperlipidemia. A single-arm open-label clinical trial with pantethine was performed in 15 patients with PKAN (92). A 24-week treatment with a dose of 60 mg/kg per day did not lead to improvement of the motor symptoms.…”
Section: Pantethine-another Alternative Substratementioning
confidence: 99%